2019
DOI: 10.1177/2152656719889030
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Hyalinizing Clear Cell Carcinoma: A Case Report and Review of the Literature

Abstract: BackgroundHyalinizing clear cell carcinomas (HCCCs) are rare, low-grade, malignant tumors which most often arise from the minor salivary glands primarily in palate and tongue but can arise in any location with minor salivary glands including the nasopharynx.MethodsA case report of primary nasopharyngeal HCCC is presented. Because of the rarity of this tumor and location, a literature search was conducted to determine the most common presenting symptoms, treatment strategies, and outcomes.ResultsA 48-year-old m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
(109 reference statements)
0
13
0
Order By: Relevance
“…Only 23 cases have been published in English, and most were single-case reports, 7,8,10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] with the complete clinical data reported for only 19. The clinical features of the 19 NHCCC cases were analyzed alongside those of the 26 new cases reported herein (N = 45).…”
Section: Discussionmentioning
confidence: 99%
“…Only 23 cases have been published in English, and most were single-case reports, 7,8,10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] with the complete clinical data reported for only 19. The clinical features of the 19 NHCCC cases were analyzed alongside those of the 26 new cases reported herein (N = 45).…”
Section: Discussionmentioning
confidence: 99%
“…Clear cell carcinoma, not otherwise specified, of minor salivary glands, also known as hyalinizing clear cell carcinoma, is an unusual primary malignancy of the nasopharynx [ 1 , 3 ]. To the best of our knowledge, there are 13 cases reported in the literature [ 5 ]. Only eight of them have complete clinical data reported (Table 1 ) [ 3 , 5 - 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are 13 cases reported in the literature [ 5 ]. Only eight of them have complete clinical data reported (Table 1 ) [ 3 , 5 - 11 ]. These tumors are microscopically characterized by a monomorphous population of cells with optically clear cytoplasm with standard hematoxylin and eosin stains [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a case series conducted by Kauzman et al, nasopharyngeal HCCC exhibited a 1% prevalence among 98 reported cases of HCCC in English literature (6). HCCC displays a higher incidence in females and typically manifests as a small, indolent mass (7). The occurrence of local or distant metastases at the time of presentation is infrequent, with no instances (0 out of 10) of nasopharyngeal HCCC presenting with distant metastases reported (6,8).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of local or distant metastases at the time of presentation is infrequent, with no instances (0 out of 10) of nasopharyngeal HCCC presenting with distant metastases reported (6,8). Symptoms associated with nasopharyngeal HCCC include otorrhea, nasal congestion, epistaxis, and tinnitus (4,7). Standard treatment approaches involve surgical resection and neck dissection in the presence of lymphadenopathy during the initial evaluation.…”
Section: Introductionmentioning
confidence: 99%